Features of growth of agricultural crops and factors negatively affecting their growth - Moldir Yessenova; Gulzira Abdikerimova; Zhanna B. Sadirmekova; Natalya Glazyrina; Saltanat Adikanova; Adilbek Tanirbergenov; Mukhamedrakhimov Karipola; Galiya Mukhamedrakhimova (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
This article is about methods of analyzing aerial images. Images from Planet.com for crops in North Kazakhstan owned by the Center for Cereal Production and Research. A.I. Barayev. The main goal of the research work is to develop and implement algorithms that allow identifying and distinguishing factors in aerial photographs that adversely affect the growth of plants during the growing season. Spectral brightness coefficient (SBC), normalized difference vegetation index (NDVI), textural features, clustering, and integral transformations are used to solve the problem. Particular attention has been paid to the development of software tools for selecting features that describe textural differences to divide texture regions into subregions. That is weeds, and pests in aerial images. The application of a set of textural features and orthogonal transformations to the analysis of experimental data is explored to identify regions of potentially correlated features in the future. The analysis of the received data made it possible to determine the characteristics of changes in the reflective capacity of agricultural plants and weeds in certain stages of the growing season. The obtained information is of great importance for confirming the observations from space remote from the aerial images.